Kualitas Penggunaan Antibiotika Pada Pasien Pneumonia Sebelum dan Sesudah Adanya Pemberian Informasi Obat Oleh Farmasis Di Bangsal Rawat Inap RSUD Kabupaten Brebes - , AGNES DWI SURYANTI; , Prof. Dr. Mustofa, M.Kes., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Based on the criteria of Gyssens, antibiotic use was rational when met the 0 criteria/category, whereas the use of antibiotics met the criteria I-VI/category known as irrational. The aim of this study was to observe the rationality usage of antibiotics before and after the provision of drug information by the pharmacist on a selection of therapies for patients with pneumonia in the ward of Brebes Public Health. This study aims to determine the rationality of the use of antibiotics before and after the provision of drug information by pharmacists to physicians in the selection of therapy for patients hospitalized pneumonia Brebes Hospital. The design of quasi experimental study, a retrospective analysis of medical records of observations in January-June 2012, the pharmacist intervention in the form of provision of drug information to physicians in the form of pneumonia, according to IDSA guidelines in 2007, and a discussion of intervals and doses of antibiotics during the month of December 2012. Prospective study in January - June 2013 against pneumonia patients inpatients wards Brebes Hospital. Evaluation of antibiotic selection was performed in all antibiotic regimens prescribed by a doctor. A total of 27 patients met the subject criteria of the retrospective study and 24 patients met the criteria of the prospective study. The results of this study showed that in the retrospective study subjects who received a single antibiotic was 65.51% and 62.50% on the prospective study, while receiving antibiotic combination on retrospective and prospective study were 20.69% and 33.33% respectively. The average length of stay (LoS) in the group receiving a single antibiotic was 4.77 days while 4.50 days on the antibiotic combination (p = 0.646 > 0,05). Quality of antibiotic use on retrospektif that met category 0 (rational) was 50% and 50% was irrational, while on the retrospective study of rational and irrational were 48,50% and 51,50% respectively with the p value = 0.897 (> 0.05). The average length of stay in the group receiving antibiotics rationally and irrationally were 4.64 (2-9) days and 4.81 (3-9) days respectively with p = 0.674 (> 0,05). The correlation between rationality antibiotic use and clinical outcome was tested with Fisher test obtained p value = 1,00 (> 0.05). There is no significant correlation in the parameters such as the duration of treatment in the hospital with antibiotics rationality, and qualitative parameters such as clinical outcomes with antibiotics rationality there is also no significant correlation. No significant correlation between on rationality use of antibiotics in pneumonia patients between before and after the provision of drug information to pharmacists in the inpatient wards at Brebes Hospital.